Article Mudrā : Code of Buddhism - Lokanang, Adirek (Journal of Buddhist Studies Chulalongkorn University, 2025)
This article aims to decode the symbolic gestures embedded in the postures of the Buddha. All Buddhas display symbolic gestures known as “Mudrā,” which is a form of expression using human fingers. These gestures are symbolic movements that convey significant spiritual meanings. The hand gestures are not only religious symbols used to create an aesthetic representation of the Buddha but can also be applied to cultivate mindfulness, concentration, and wisdom. It is said among Buddhists that when one practices meditation habitually, they can access the true mental path of the Buddha. Such a person will exhibit slow, gentle, composed movements, embodying full mindfulness, while also being stable and firm. The mindful movements of those with complete awareness form the basis of “Mudrā,” reflecting the gestures of the Buddha and his disciples, who maintain morality, mindfulness, concentration, and wisdom in an interconnected chain. These Mudrā gestures, therefore, conceal the most essential qualities: morality and the cultivation of mindfulness, leading to profound and seamless concentration.